Literární autenticita jako placebo politiky. Lopatka, Viewegh a další v diskusích devadesátých let - Hana Blažková (Slovo a Smysl, 2020)
This paper aims to analyze the so-called disputes over authenticity which took place in the early 1990s, from the perspective of a political reading. It attempts to reconstruct the diferent meanings of the term authenticity and to show that these disputes were mainly politically motivated. Te frst part tries to fnd an explanation for the (declared) depoliticization of Czech literature and literary criticism afer 1989, in comparison with the broader (Central) European context and ‘anti-political politics’ of Czech dissent. The second part is focused on the discussion and polemics concerning authenticity in the context of literary magazines. It aims to analyze the positions of individual actors (Bílek, Fidelius, Janoušek, Špirit, etc.) in order to understand their political ramifcations. Te third part focuses on the popularity of so-called authentic (biographical) literature and on the ways in which Michal Viewegh employs it in his writings.